Hair growth potential of Helianthus annuus seed oil extract and Martynia annua seed oil extract on albino mice (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The surface scalp of hair matrix cells differentiation during migration induces by vigorous proliferation result hair growth. The objective of current investigation was to explore the needs to know of Helianthus annuus seed oil extract and Martynia annua seed oil extract as a potential of hair growth. In albino mice on to the back skin surface spread prepared oil extract to assess telogen to anagen phase transition. The quantitative and qualitative analysis was performed and observed. The outcomes of their research revealed that Helianthus annuus seed oil extract of petroleum ether and Martynia annua oil extract of petroleum ether in combination shows exhibited prominent activity. In different dosage of petroleum ether oil extract of both plant combinations of dosage applied topically 10 mg/ml, 20 mg/ml and 30 mg/ml, in to the shaved skin of albino mice treated groups observed for 21 days. Result shown that petroleum ether oil extract of both plant in combination shown significantly hair growth potential in a different dosage dependent manner observed, particularly on albino mice. Albino mice groups treated with petroleum ether 30 mg/ml of both plants required shorter time to the control (positive) group and 2% minoxidil (standard) group at different growth stages. The hair length of albino mice treated with petroleum ether 30 mg/ml oil extract of both plants showed remarkable increase 21.35±0.25 mm. and the thickness of hair of albino mice group treated with combination of both plant oil extract is 0.020±0.0010 mm with respect to 2% minoxidil (0.021±0.008). These finding suggested that Helianthus annus seed oil extract and Martynia annua oil extract have the potential of show hair growth.